Reproduction and conservation of the leatherback turtle Derrnochelys coriacea (Testudines: Dermochelyidae) in Gandoca, Costa Rica - Chacón, Didiher; McLarney, William; Ampie, Carlos; Venegas, Benson (Revista de Biología Tropical, 1996)
The leatherback turtle was studied in Gandoca, an important nesting beach on the southeas tem Caribbean coast of Costa Rica (820 37’ W; 090 37’ N). In 1994, a total of 530 nests was recorded during the nesting season (February/July) and 160 leatherbacks were tagged; five were remigrants from the 1992 season and 15 carried tags from elsewhere. Eighty eight females only nested once. Mean curve carapace measurements were 1ength 153.8 cm and width 112.0 cm. A hatchery received 82 clutches, with 6277 normal eggs. Their mean incubation period was 62.24 days (range: 56-68 days). Average hatching rate was 55.10% (S.D. : 25.04, range 15-96%). Extensive erosion, beach debris and poaching activity represent the main hazards for nesting in Gandoca